Sintesis dan Karakterisasi Arang Aktif Dari Kulit Salak Sebagai Adsorben Terhadap Kadar BOD, COD dan TSS Pada Limbah Cair Industri Tekstil - Barita Aritonang; Nova Florentina Ambarwati; Eka Margaretha Sinaga; Ahmad Hafizullah Ritonga (PT FORMOSA CENDEKIA GLOBAL, 2022)
Textile liquid waste contains organic compounds and suspended solids such as BOD, COD, and TSS, which can cause environmental pollution. This study aims to determine the levels of BOD, COD, and TSS in textile wastewater using activated charcoal from the skin of salak before and after activation with phosphoric acid (H3PO4) at a concentration of 6%.The research results that have been carried out, on the making of activated charcoal from the skin of salak have been successfully carried out and meet the requirements of SNI 06-3730-1995, obtaining 2.4% water content, 2.3% ash content, and 476 mg/L iodine absorption. FT-IR spectrum analysis activated charcoal from the skin of salak has an O-H hydroxyl group at the peak of 3817 cm-1, C=O carbonyl group at 1713 cm-1, and C-O ether group at 1175 cm-1. FT-IR spectrum analysis activated charcoal from the skin of salak has O-H hydroxyl group at the peak of 3817 cm-1, C=O carbonyl group at 1713 cm-1, and C-O ether group at 1175 cm-1. Based on SEM analysis, activated charcoal from activated skin of salak has larger pores and surface area than before activation. Based on atomic absorption spectrophotometry analysis of textile wastewater without the addition of activated charcoal, the levels of BOD were 480 mg/L, COD 650 mg/L, and TSS 470 mg/L. After the addition of unactivated activated charcoal, the levels of BOD were 120 mg/L, COD 150 mg/L, and TSS 140 mg/L. After the addition of activated charcoal, BOD levels were 60 mg/L, COD 80 mg/L, and TSS 95 mg/L.This study concludes that activated charcoal from the skin of salak can reduce, levels of BOD, COD, and TSS in textile waste and has met the requirements set out in the Regulation of the Minister of the Environment of the Republic of Indonesia Number 5 of 2014.